Benefit, Problems and Solutions of Using Online Media in Studies with Efficiency in Schools, Nakhon Si Thammarat Province - จำเนียร เมธาวี; จำเนียร กรกฎ (Ratchaphruek Journal, 2018)
This research was studying benefit, problems and solutions of using online media in studies with efficiency in schools. The researchers use focus group with purposive samples who are students and teachers from 7 schools in Muang District, Nakhon Si Thammarat Province. The result show a benefit of using online media in studies which has a lot of issues. The samples express accordingly that online media is the tool for searching additional information in subjects; in particular, YouTube. Moreover, online media supports communication among friends, between teachers and students. It helps to translate many languages; especially, English. For teachers, online media is beneficial by using in teaching, online lessen and management. However, big problem of online media for teaching is students who play smartphone while teaching; especially, games. There is also using information from unreliable source in online media, copying all information without analysis and reference, using online media too much and using unappropriated language in online media. Therefore, the solutions of these problems are producing media attracting students’ interest and they can participate in media production. Most of samples propose short video clip give knowledge in using properly online media in studies. They may be short film uploaded in social media, training, exhibition about proper media using, games, and voice on the line, radio programming and online media for teaching.